Information on Intellectual Capital in the Financial Statements and Annual Activity Reports of Pharmaceutical Companies - Mataczyna, Krzysztof; Wielgórska-Leszczyńska, Joanna (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2020)
Objective: The aim of the article is to examine the detailed disclosure of information on intellectual capital in the financial statements and annual activity reports in 2017 and 2018 of pharmaceutical companies registered in Poland and listed on the Warsaw Stock Exchange.Research Design & Methods: The study was preceded by a review of the literature on the subject, including scientific articles, monographs, industry reports and legal acts. The study is based on the examination of financial statements and annual activity reports of the analysed companies.Findings: The companies examined do not prepare separate reports on intellectual capital, but include the information in their activity reports and financial statements. There is no standardised way for that information to be included.Implications / Recommendations: The differentiation characterising the information disclosed on intellectual capital confirms the need to standardise information on intellectual capital disclosed in activity reports and financial statements.Contribution: This study can be treated as an introduction to the wider research on the disclosure of information about intellectual capital in the pharmaceutical industry, as well as on the importance of intellectual capital for the companies’ financial condition.